Comportamientos del profesor universitario y éxito académico de los estudiantes de los grados de maestro de infantil y primaria - Gil Madrona, Pedro; García-Gómez-Heras, Soledad; Hernández-Barrera, Valentin; Lopez-de-Andres, Ana; Lopez-Gomez, Laura; Fernández-García, Hector; Diaz-Suarez, Arturo; Carrasco-Garrido, Pilar (Anales de Psicología / Annals of Psychology, 2016)
It´s disturbing to think about the idea that the teacher can lead a student to achieve great successes or, on the contrary, beat him academically. It´s for this reason that it´s necessary to explore the behavior of teaching professionals, from the point of view of the student, to know which ones they consider that will impact positively on their academic success. In order to this, a sample of 486 pupils from grades Primary Education Teachers (199) and Primary (287) in the Faculty of Education of Albacete (University of Castilla La Mancha) Education was analized. A questionnaire (Tuncel, 2009) (from few questions and the type of response ) was applied and, using a Factor Analysis Exploratory, there were found six dimensions to which the students gave the highest importance: "Emotional aptitude of teachers " ; " Teacher-student interaction " ; " Achieving the goals of education" , "Connecting between teaching of theory and practices " ; "Planning and organization of teaching " ; "Correct and provide information to students about their advance and progress."